Developing EFL Student's Narrative Writing through Storybird Application - Madinatul Munawaroh; Feri Ferdiyanto; Zainuddin Zainuddin (Universitas Pahlawan Tuanku Tambusai, 2026)
Writing is one of the most challenging skills in English as a Foreign Language (EFL) learning because it requires students to combine language knowledge, idea development, and organization at the same time. Many students still experience difficulties in starting their writing, developing ideas, and organizing their stories into a clear structure. This study aims to investigate the implementation of the Storybird application in teaching narrative writing and to describe how students’ narrative writing skills develop through its use. This research employed a qualitative design conducted at MTs Raudhatul Hasaniyah involving 14 students. Data were collected through classroom observation, interviews, and document analysis of students’ narrative texts. The findings showed that Storybird helped students generate ideas more easily, organize their narratives better, and become more engaged in writing activities. The visual prompts provided by the application supported students in developing coherent stories and increased their confidence in writing. The learning process also became more interactive and enjoyable. These results indicate that Storybird is an effective tool to support the development of students’ narrative writing skills in EFL classrooms.